2017
DOI: 10.1021/acs.jmedchem.7b00648
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Diphenyl Conjugated Imidazole Derivatives as Potential Glutaminyl Cyclase Inhibitors for Treatment of Alzheimer’s Disease

Abstract: High expression of glutaminyl cyclase (QC) contributes to the initiation of Alzheimer's disease (AD) by catalyzing the generation of neurotoxic pyroglutamate (pE)-modified β-amyloid (Aβ) peptides. Preventing the generation of pE-Aβs by QC inhibition has been suggested as a novel approach to a disease-modifying therapy for AD. In this work, a series of diphenyl conjugated imidazole derivatives (DPCIs) was rationally designed and synthesized. Analogues with this scaffold exhibited potent inhibitory activity agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 35 publications
0
36
0
Order By: Relevance
“…Li et al reported a group of diphenyl conjugated imidazole analogues as potential QC inhibitors (Figure ). Alkyl substitution for R 3 , R 4 , R 5 significantly decreased inhibitory activity, but the activity was improved when R 3 was replaced by a fluorine atom.…”
Section: Qc Iinhibitorsmentioning
confidence: 99%
“…Li et al reported a group of diphenyl conjugated imidazole analogues as potential QC inhibitors (Figure ). Alkyl substitution for R 3 , R 4 , R 5 significantly decreased inhibitory activity, but the activity was improved when R 3 was replaced by a fluorine atom.…”
Section: Qc Iinhibitorsmentioning
confidence: 99%
“…Synthesized compounds showed potent inhibitory activity against human glutaminyl cyclase along with high blood-brainbarrier permeability and could substantially reduce the level of amyloid plagues in the brain. The nitrogen atom of imidazole ring binds to the catalytic zinc ion at the pocket of glutaminyl cyclase to inhibit the enzyme [4]. A novel series of triazole containing mammalian target of rapamycin (mTOR) kinase inhibitors were synthesized and their potency, selectivity and pharmacokinetics were evaluated ( Figure 5).…”
Section: Bioactivities Of Nitrogen Rich Heterocyclesmentioning
confidence: 99%
“…Also, thiobarbiturates are broadly used for the synthesis of diverse complexes [20,21], being employed as a reagent for spectrophotometric investigation of numerous metals [2023], to determine the oxidation degree of natural fats in nutrients [2426] and industrially as thermal stabilizers for rigid poly(vinyl chloride) at high temperature [27]. Imidazole motif exists widely in different types of naturally occurring and synthetic pharmaceutical compounds and displays assortment of pharmacological activities [2830]. Moreover, imidazole derivatives are used as building blocks in natural product synthesis [31], catalysis [32] and coordination chemistry [33].…”
Section: Introductionmentioning
confidence: 99%